2021
DOI: 10.1029/2020jb021434
|View full text |Cite
|
Sign up to set email alerts
|

Stacked Magma Lenses Beneath Mid‐Ocean Ridges: Insights From New Seismic Observations and Synthesis With Prior Geophysical and Geologic Findings

Abstract: Recent multi‐channel seismic studies of fast spreading and hot‐spot influenced mid‐ocean ridges reveal magma bodies located beneath the mid‐crustal Axial Magma Lens (AML), embedded within the underlying crustal mush zone. We here present new seismic images from the Juan de Fuca Ridge that show reflections interpreted to be from vertically stacked magma lenses in a number of locations beneath this intermediate‐spreading ridge. The brightest reflections are beneath Northern Symmetric segment, from ∼46°42′‐52′N a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 89 publications
(200 reference statements)
4
46
0
Order By: Relevance
“…The periodicity of melt supply and the fluctuation of the thermal regime documented at fast spreading ridges (Marjanović et al., 2014; Soule et al., 2009) are much lower than at slow and ultraslow ridges (Chen et al., 2021; Klischies et al., 2019). The predictions of our simulations are, however, consistent with the dynamics of magmatic systems documented at the gabbro/sheeted dikes transition zones of the Oman ophiolite and the fast spreading East Pacific Rise (Carbotte et al., 2021; Gillis, 2008; Nicolas et al., 2008). The AMLs migrate upward during waxing phases, corresponding to the reheating of the AML roof and hence the recrystallization of hydrothermally altered sheeted dikes into pyroxene and hornblende hornfels with the formation of xenoliths, while during waning phases, AMLs migrate downward, causing crystallization at the AML roof and/or sides to form isotropic gabbros that are crosscut by later dikes (France et al., 2009; Gillis, 2008; Nicolas et al., 2008, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…The periodicity of melt supply and the fluctuation of the thermal regime documented at fast spreading ridges (Marjanović et al., 2014; Soule et al., 2009) are much lower than at slow and ultraslow ridges (Chen et al., 2021; Klischies et al., 2019). The predictions of our simulations are, however, consistent with the dynamics of magmatic systems documented at the gabbro/sheeted dikes transition zones of the Oman ophiolite and the fast spreading East Pacific Rise (Carbotte et al., 2021; Gillis, 2008; Nicolas et al., 2008). The AMLs migrate upward during waxing phases, corresponding to the reheating of the AML roof and hence the recrystallization of hydrothermally altered sheeted dikes into pyroxene and hornblende hornfels with the formation of xenoliths, while during waning phases, AMLs migrate downward, causing crystallization at the AML roof and/or sides to form isotropic gabbros that are crosscut by later dikes (France et al., 2009; Gillis, 2008; Nicolas et al., 2008, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…However, most scientists believe that the magmatic processes responsible for magmatic accretion at fast‐spreading oceanic crust are too complex to be explained with such simple end‐member models, and that the truth probably lies somewhere in between these models (Boudier et al., 1996; Maclennan et al., 2004; Natland & Dick, 2009). Such hybrid models are also supported by the estimation of crystallization depths of MORB (Wanless & Shaw, 2012) and from recent multi‐channel seismic studies indicating the presence of deep melt sills under recent fast/intermediate‐spreading ridges (e.g., Canales et al., 2009; Carbotte et al., 2012, 2021; Marjanovic et al., 2014; Nedimovic et al., 2005).…”
Section: Introductionmentioning
confidence: 67%
“…So the initial thickness of the melt lens remains unconstrained as of today. For stacked deep magma lenses in the plutonic crust at the Juan de Fuca Ridge which were investigated using seismic experiments, Carbotte et al (2021) recently estimated a maximum thickness of the observed melt reservoirs of 140-170 m.…”
Section: Hybrid Formation Of the Lower Oceanic Crust In The Wadi Gideahmentioning
confidence: 99%
“…We tentatively draw the contours of this hot and melt‐bearing domain down to Moho depth, where we propose that it roots into the melt‐bearing upper mantle (Figure 9c). Inspired by observations of stacked melt sills at fast and intermediate spreading ridges (Carbotte et al., 2020, 2021; Marjanović et al., 2014), and by a conceptual model of the transcrustal magma plumbing system beneath subaerial volcanos (Cashman et al., 2017), we also propose that some of the melt in this hot lower crustal region resides in vertically stacked melt lenses (Figure 9c), and that these lenses play a role in transferring melt from the mantle to the upper crust to feed eruptions. In Figure 9c, we also infer that most hydrothermal cooling occurs in a domain that is, limited both by temperature (ca 600°C) and pressure (corresponding to depths <6 km) as proposed by Morgan and Chen (1993).…”
Section: Discussionmentioning
confidence: 99%